The Implementation of Religious Culture for Prathom Level in Bakong Pittaya School Pattani, Thailand - Zakiyati, Isna Imroatuz (Universitas Islam Negeri Raden Intan Lampung, 2018)
The aim of this research is to describe the implementation of religious culture in the prathom (elementary) level in Bakong Pittaya School Pattani, Thailand. The type of the research is field research. The data collecting method used in this study are observation, interview, and documentation. From the result of research, the writer found that the implementation of reaching religious culture is using the instructive sequential strategy through creating the religious atmosphere, values internalization, good example, habituation, and civilizing religious culture. Meanwhile, in civilizing religious culture, this school uses the power strategy with the reward-punishment approach and persuasive strategy with the habituation and exemplary approach. Moreover, there are 14 religious culture forms in the prathom level of Bakong Pittaya School, Pattani, Thailand.